Early Detection of Chronic Obstructive Pulmonary Disease by Following Individual Annual Changes in Lung Function - Utsumi, Kenta; Naruto, Mamiko; Ichinose, Yuichi; Noro, Mitsuko; Torii, Yasushi; Kasuga, Ikuma; Minemura, Kazushige; Yonemaru, Makoto; Kiyokawa, Hiroshi; Toyama, Keisuke (Nihon Kyōbu Shikkan Gakkai zasshi, 1993)
The possibility of early detection of chronic obstructive pulmonary disease (COPD) was investigated among subjects whose lung function could be followed for more than ten years. Ten subjects aged 60 or more were selected from among about 1500 cases using the following diagnostic criteria; (1) subjects had complained of exertional dyspnea (2) chest X-ray abnormalities were suggestive of COPD (3) FEV1.0% was under 55%. Data on FVC/height, FEV1.0/height and FEV1.0% of these subjects were available for the previous ten years. Individual linear regression equations were estimated. Average annual changes of cases of obstruction were compared with those of normal cases, and individual deviations from the normal standard range were observed. Declines of the regression lines were as follows; FEV1.0/height: normal case -0.016±0.017, obstruction cases -0.038±0.018 (L/m/yr), FEV1.0%: normal cases 0.164±0.627, obstruction cases -1.522±0.638 (%/yr). Significant differences were observed between the normal and the obstruction cases (p<0.01). FEV1.0% of all obstruction cases was under -2 SD of that of normal subjects. All individual FEV1.0% regression lines of the obstruction cases were outside ±2 RSD of the normal standard range more than 5 years before the onset of symptoms. Following individual annual changes in lung function was considered to be useful for the early detection of COPD.